The influence of skepticism on cause-related marketing campaigns on behavioral intention of muslim millennials in Indonesia: The role of satisfaction as mediators and religiosity as moderators - Sakinah, Zahrah Riski; Gayatri, Gita (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: In today’s competitive business, companies cannot rely solely on functional excellence to maintain competitiveness. Therefore, more creative marketing strategies, such as cause-related marketing (CRM), are increasingly being implemented, especially to address the social consciousness of consumers, especially the millennial generation. However, a major challenge for marketers is consumer skepticism, which can reduce the effectiveness of CRM campaigns. This study aims to explore the factors that influence consumer perceptions of marketing claims that generate skepticism and their impact on consumer behavior, especially among Indonesian millennial Muslims. Methods: This study employs a quantitative approach using a survey method to collect data from Indonesian millennial Muslims who have engaged with CRM promotions in the past year. The data will be analyzed using Covariance-based Structural Equation Modeling (CB-SEM) with IBM AMOS 26 to examine the relationships between variables, as well as the mediating role of satisfaction and the moderating effect of religiosity on the skepticism-behavior intention relationship. Findings: The study is expected to reveal key factors that influence skepticism in CRM campaigns and their subsequent effect on consumer behavior. Additionally, it will investigate how satisfaction mediates the skepticism-behavior intention link and the role of religiosity in moderating these relationships. Conclusion: The findings will contribute to a deeper understanding of consumer skepticism in CRM campaigns, particularly in the context of millennial Muslims in Indonesia. The study will also provide insights into the influence of religiosity and satisfaction in shaping consumer responses to marketing claims. Novelty/Originality of this article: This research is original in its focus on the millennial Muslim demographic in Indonesia, exploring the unique factors that drive skepticism in CRM campaigns. The study also introduces the moderating role of religiosity, a variable often overlooked in marketing studies. Furthermore, it provides valuable insights into the mediating effect of satisfaction on consumer behavior in the context of CRM.